2017
DOI: 10.1021/acs.jafc.7b02190
|View full text |Cite
|
Sign up to set email alerts
|

Soybean P34 Probable Thiol Protease Probably Has Proteolytic Activity on Oleosins

Abstract: P34 probable thiol protease (P34) and Gly m Bd 30K (30K) show high relationship with the protease of 24 kDa oleosin of soybean oil bodies. In this study, 9 day germinated soybean was used to separate bioprocessed P34 (P32) from bioprocessed 30K (28K). Interestingly, P32 existed as dimer, whereas 28K existed as monomer; a P32-rich sample had proteolytic activity and high cleavage site specificity (Lys-Thr of 24 kDa oleosin), whereas a 28K-rich sample showed low proteolytic activity; the P32-rich sample containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Due to the slight band intensity changes of 11S and 7S globulins and caleosins at 30 °C, it was suggested that the band intensity increase at the position for oleosin‐L was induced by the hydrolyzed products of oleosin‐H, which had similar MW to oleosin‐L. This phenomenon was also occurred in the isolated soybean OB, in which P34 probable thiol protease hydrolyzed 24 kDa oleosins into hydrolyzed products with similar MW to 16 kDa oleosins (Zhao et al, 2017). With increasing temperature from 40 to 70°C, oleosin‐H disappeared, and re‐appeared at 80°C.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Due to the slight band intensity changes of 11S and 7S globulins and caleosins at 30 °C, it was suggested that the band intensity increase at the position for oleosin‐L was induced by the hydrolyzed products of oleosin‐H, which had similar MW to oleosin‐L. This phenomenon was also occurred in the isolated soybean OB, in which P34 probable thiol protease hydrolyzed 24 kDa oleosins into hydrolyzed products with similar MW to 16 kDa oleosins (Zhao et al, 2017). With increasing temperature from 40 to 70°C, oleosin‐H disappeared, and re‐appeared at 80°C.…”
Section: Resultsmentioning
confidence: 97%
“…Several studies have confirmed that plant seed endogenous endopeptidases are contained in the isolated OB, and they can hydrolyze the intrinsic and extrinsic proteins of OB (Chen et al, 2018; Vandana & Bhatla, 2006; Zhao et al, 2016, 2017). However, few studies have checked whether these endogenous endopeptidases can efficiently demulsify the OB.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Exogenous proteins include lipoxygenase and glycinin (A 3 , acidic peptide chain, basic peptide chain), β‐conglobulin (α, α', and β), γ‐conglobulin, Bd 30K, and P34 (Chen, Cao et al., 2014; Chen, Zhao et al., 2014). It was reported that P34 was an protease that had proteolytic activity and high cleavage site specificity (Lys‐Thr of 24 kDa oleosin) (Zhao et al., 2017). Some researches showed that endogenous protease P34 of SOB enrichment extracted at the conditions of pH 6.5, room temperature, and water phase could hydrolyze 24 kDa oleosin to peptides (16 kDa and 8 kDa) within 1 hr (Zhao, Chen, Cao, et al., 2013; Zhao, Chen, Zhang, et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous proteins include lipoxygenase and glycinin (A 3 , acidic peptide chain, basic peptide chain), β-conglobulin (α, α', and β), γ-conglobulin, Bd 30K, and P34 . It was reported that P34 was an protease that had proteolytic activity and high cleavage site specificity (Lys-Thr of 24 kDa oleosin) (Zhao et al, 2017).…”
Section: Effect Of Wbae Temperature On Protein Components In Sob Enmentioning
confidence: 99%